Petasma as a Reliable External Indicator of Male Sexual Maturity in Penaeus schmitti : Integrating Morphological, Biometric and Histological Analyses - H. Castro‐Neto; C. Craveiro; M. G. do Rêgo; P. G. V. Oliveira; R. Soares; S. Peixoto (Fisheries Management and Ecology, 2026)
Understanding male sexual maturity in penaeid shrimp is crucial for stock assessment and size‐based management; however, maturity criteria remain heavily biased toward females and rarely validated for males. This study evaluated whether petasma fusion is a reliable external indicator of male sexual maturity in white shrimp Penaeus schmitti from Northeast Brazil and estimated size at first maturation using an integrative morphometric, histological, and statistical approach. Forty‐five males were classified according to petasma condition, morphometrically measured, histologically examined along the reproductive tract, and analyzed using individual‐level binomial logistic regression. The estimated cephalothorax length at first maturation was CL 50 = 2.24 cm (95% CI: 2.06–2.43), with a strong model performance (Nagelkerke R 2 = 0.80). Histological analysis revealed complete categorical agreement between external morphology and internal reproductive status: all males with unfused petasma lacked mature spermatozoa and exhibited only early germ cells, whereas all males with fused petasma presented the complete spermatogenic series and fully differentiated spermatozoa in the terminal ampulla. The relationship between petasma length and body size showed negative allometry, indicating a proportionally smaller investment in petasma growth relative to somatic growth. ANCOVA detected a significant maturity effect on the intercept, but not on the slope, demonstrating a discrete proportional change in petasma dimensions at maturation, rather than a change in growth trajectory. These findings demonstrate that petasma fusion is a robust and nondestructive indicator of physiological maturity in male P. schmitti . The results of the analysis combining petasma, histology, and length at first maturity indicated that petasma is a reliable indicator for validating physiological maturity and that male reproductive indicators should be formally incorporated into penaeid fishery management structures.